A Reflex Algebraic Reserve Constraint Model - Chavez-Orostica, H; Lismayes-Aguilar, A (Institute of Electrical and Electronics Engineers Inc., 2020)
The Renewable Energy FLEXibility model (REFLEX) is a planning model that assesses the impact of renewable integration on power balance flexibility. As the model has been implemented in various commercial software, it is currently a known framework to evaluate planning scenarios of renewable integration. In order for the model to represent flexibility related to intra-dispatch system balance, an iterative process has to be performed to evaluate the adequacy of reserve coordination for all commitment decisions through dynamic simulations. This process is computationally intense, and must be performed each time the system changes. This work proposes a general model to represent intra-dispatch reserve adequacy algebraically, so the iterative process is avoided. A numerical example is provided. © 2020 IEEE.